Degree of Chitosan Deacetylation: Potential of Experimental Equations Application - Nadežda Seratlić; Nevena Hromiš; Senka Popović; Danijela Šuput; Jovana Pantić; Ivana Čabarkapa (Kemija u Industriji, 2024)
In recent years, research has extensively explored the broad industrial potential of chitosan, with the degree of deacetylation being a pivotal chemical attribute that significantly influences its physical and biological properties crucial for its various applications. Numerous methods have been developed to determine the degree of deacetylation: linear potentiometric titration, infrared spectroscopy, nuclear magnetic resonance spectroscopy, pyrolysis-mass spectrometry, UV spectroscopy, and titrimetry. The challenge for researchers lies in selecting an appropriate method due to factors like time consumption, costliness (notably nuclear magnetic resonance spectroscopy), and the potential for sample destruction inherent in certain methods. Among these, infrared spectroscopy has emerged as a preferred method due to its speed and non-destructive nature. This study investigated the use of experimental equations, as documented in the literature, to determine the degree of chitosan deacetylation under laboratory conditions using three chitosan samples differing in viscosity, each having a documented degree of deacetylation above 75 %. Three distinct methods – potentiometric titration, acid-base titration, and Fourier transform infrared spectroscopy – were employed to calculate chitosan's deacetylation degree. While acid-base and potentiometric titration showcased simplicity in terms of equipment, the latter proved more time-consuming. In contrast, infrared spectroscopy demands more intricate instrumentation but requires only minimal samples, ensuring rapid analysis. The results showed that the methods of infrared spectroscopy and acid-base titration, using reported experimental equations, can be used to determine the degree of chitosan deacetylation. However, potentiometric titration did not validate its efficacy for this purpose.